ANALISIS BAURAN PEMASARAN DALAM MENINGKATKAN VOLUME PENJUALAN PRODUK TUPPERWARE (Studi Pada Unit Elit Direktur Rayyen Tupperware Ujungbatu) - Nadita Yulia Putri; Lie Othman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study aims to determine and analyze marketing mix ( quality _ product , determination price , strategy promotion and location ) in increasing sales volume in Elite Units Director Rayyen Tupperware Ujungbatu . This study uses a quantitative descriptive analysis method with the SPSS program version 25 . The population in this study is all There are 300 members of the Rayyen Tupperware Ujungbatu ED Unit and the sample of this study was 169 respondents from members of the Ujungbatu Rayyen Tupperware ED Unit . Determination of the sample in this study using the Krijie formula and M organ , namely the purposive sampling technique . For technique data collection through questionnaire and studies library , type and data sources using primary data and secondary . Data collection techniques using Scale Likert . Results study confirm existence influence quality product , determination price , strategy promotion and location in increase sales volume .Keywords: Product Quality, Pricing, Strategy Promotion , Location , Sales Volume